A facile method of preparing highly porous polylactide microfibers. Issue 7 (23rd October 2017) - Liu, Qingsheng; Yang, Qibing; Zhou, Yuqi; Zhao, Mingming; Shen, Ying; Zhou, Fenglei; Gong, R Hugh; Deng, Bingyao
ABSTRACT: Highly porous polylactide (PLA) microfibers with the diameter of about 14 µm are prepared by melt‐spinning and stretching core–sheath PLA fibers (CSF) and sequent treatment of ethyl acetate. The resultant pores are regular and elliptical. The average values of length of major axis and minor axis of elliptical pores are around 1 and 0.5 μm, respectively. This new and facile method can prepare porous PLA fibers on industrial scale, and nearly overcome all the shortcomings of melt‐spinning and stretching method. In addition, highly porous structure in partially oriented poly(l ‐lactide) yarn (POY) can be also formed by treating POY using ethyl acetate. The obtained pores are irregular. In addition, the formation mechanism of pore structure in CSF is different with the one in POY. The former is the separation of row‐nucleated lamellae induced by stretching while the latter is swelling and subsequent solvent‐induced crystallization. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45860. Abstract :